Farms expectations concerning individual projects in mountain areas of Tlemcen province (Algeria) - Hattab, Mourad; Gaouar, Abdelaziz (Comunicata Scientiae, 2017)
The present work aims to analyze the expectations of farms concerning the Proximity Projects of Integrated Rural Development (PPDRI) which could be implemented by the Algerian government in rural areas in general, and in mountainous areas in particular. For that, 122 farms have been surveyed in three mountainous regions (Ain Fezza, El Gor and Sidi Djilali) belonging to the mountains of Tlemcen which are north-west of Algeria. The results obtained showed that expectations of farms, in terms of individual projects desired to be made, differ from one region to another. Moreover, the heads of surveyed farms retain a remarkable awareness vis-à-vis agricultural projects that are better suited to the potential of their mountainous areas. In addition, the development of certain high-value agricultural activities which appear despised by many farms and can contribute in a significant way to improve their income sources, requires from the start a considerable improvement of technical assistance proves insufficient in these disadvantaged areas. Finally, public authorities should know good value the projects formulated by farms, and readjust its funding according to the particularities of these areas which are poor and characterised by difficult natural constraints.